Bridging cultural heritage information on the web: A metadata model-based approach for information aggregation in South and Southeast Asian cultural heritage - Wijesundara, Chiranthi; Sugimoto, S. (Library, University of Colombo, Sri Lanka, 2018)
The web has brought the whole world to our fingertips and it has made distant cultural heritage more accessible than ever. The Cultural Heritage Information (CHI) on the web is primarily created and organised by memory institutions as digital archives and is provided to the public. In addition, there are many third-party institutions and individuals who create CHI and/or add value to existing CHI on the web. Thus, there is numerous CHI on the web, but in the reality, they exist in unconnected silos. This situation is common in the South and Southeast Asia, and in addition, the region has its own problems associated with organisation and dissemination of CHI. The authors have investigated these factors and developed a novel metadata model which enables the organisation of both, tangible and intangible cultural heritage separately. The model enables users to distinguish between physical and digital environments of cultural heritage resources and its goal is to aggregate related digital cultural heritage resources to a single platform. It is essential to properly identify the objects which convey information of Cultural Heritage Objects and describe them in accordance with their features, e.g., online digital archives and third-party websites. As a result, the authors have introduced a concept called Modular Metadata which enables the identification of original cultural heritage objects and their digital surrogates separately. Proposed models were evaluated using few use cases and schema mapping was done to examine the feasibility in real-world situations.
Keywords: cultural heritage information; information organisation; metadata aggregation; modular metadata; South and Southeast Asia